Business process management : a rigorous approach - Ould, Martyn A., 1948- (British Computer Society, 2005)
Businesses need to adapt constantly, but are often held back by static IT systems. The 'Riva approach to Business Process Management' is a way of analysing the mass of concurrent, collaborative activity that goes on in an organisation, providing a solid basis for developing flexible IT systems that support a business.